Community Participation in the Development Planning Process of the Village Area - Ahmad Ahmad; Barkah Rosadi; Susniwati Susniwati (Trescode Green Organization, 2024)
The implementation of mandatory actions required by Law No. 23 of 2014 concerning Regional Government, Article 150, mandates that development planning is a mandatory affair. Development planning as carried out in Sekeloa Sub-District is through a participatory planning process known as